Polycaprolactone-based functional polyurethane material as well as preparation method and application thereof

By introducing degradable structures such as hexahydrotriazine and polyester polyol into the polyurethane material, polycaprolactone-based functional polyurethane materials with reversible dynamic covalent bonds of ester groups and hexahydrotriazine rings, the polyurethane material has been solved. The difficult degradation problem in the environment has achieved the chemical and biomultiple degradation properties of materials and improved their application potential in the fields of medical and biomedical science.

CN119463090AActive Publication Date: 2025-02-18GUANGXI UNIV FOR NATITIES

Patent Information

Application Number
CN202411728026.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-18
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Existing polyurethane materials are difficult to degrade in the environment, resulting in severe damage to the environment and ecosystems. At the same time, their degradability and biocompatibility are insufficient, limiting their application in the medical and biomedical fields.

Method used

By introducing degradable structures such as hexahydrotriazine and polyester polyol into isosorbate-based polyurethane materials, a polycaprolactone-based functional polyurethane material with reversible dynamic covalent bonds of the ester group and the hexahydrotriazine ring is formed. The material is prepared in a non-catalytic system and has good biocompatibility and shape memory functions.

Benefits of technology

The chemical and biomultiple degradation performance of polyurethane materials has been achieved, which has improved its application potential in the fields of medical materials and flexible sensors, and has rapid and complete degradation capabilities in the environment, reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463090A_ABST
    Figure CN119463090A_ABST
Patent Text Reader

Abstract

The invention discloses a polyurethane material with a shape memory function and dual degradability as well as a preparation method and application thereof, and belongs to the field of functional polyurethane materials. The preparation method of the polyurethane material comprises the following steps: melting and mixing isosorbide and polycaprolactone glycol in a nitrogen atmosphere, then adding a diisocyanate monomer to react for 9-12 hours, finally adding a chain extender hexahydro-1, 3, 5-tris (hydroxyethyl)-s-triazine, stirring for 30 minutes, pouring a reaction mixed solution into a polytetrafluoroethylene mold, and curing at 80 DEG C to obtain a polyurethane film. According to the invention, the ratio of an isosorbide rigid structure unit to a hexahydrotriazine cross-linked structure unit is finely regulated and controlled, so that the dual-degradability polyurethane with both chemical degradability and biodegradability is obtained. The polyurethane prepared by the invention also has good mechanical properties and biocompatibility and shows a good shape memory function, and the shape fixation rate (Rf) and the shape recovery rate (Rr) are both greater than 90%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of functional polyurethane materials, and in particular to a polycaprolactone-based multifunctional polyurethane material integrating biocompatibility, shape memory function and dual degradability, a preparation method and application thereof. Background Art

[0002] Based on its excellent mechanical properties, performance adjustability and low overall cost, polyurethane is widely used in many fields. However, discarded polyurethane products exist in the environment for a long time, causing serious damage to the environment and ecosystem.

[0003] In order to solve the environmental and ecological problems caused by polyurethane materials and their sustainable development problems, researchers have tried to introduce degradable structures and biomass resources into the preparation of polyurethane materials in the past few decades. For example, the use of bio-based green polyols to prepare polyurethane products is one of the effective means to alleviate the resource crisis. However, polyurethanes prepared solely by replacing petroleum-based raw materials with biomass raw materials, especially cross-linked polyurethane materials, still have problems such as low degradation rate and incomplete degradation in terms of degradability.

[0004] Due to the irreversible cross-linked structure of thermosetting materials, high temperature, special solvents or strong oxidants are usually required to cleave chemical bonds, resulting in huge challenges in terms of rapid degradation and efficient recycling. The key to solving this challenge is to synthesize polyurethanes containing reversible dynamic covalent structures. Reversible dynamic covalent bonds mainly include ester bonds (OC=O), acetal bonds (-O-CH(CH3)-O-), disulfide bonds (-SS-), imine bonds (-C=N-) and hexahydrotriazine (hydroxyethyl hexahydrotriazine) structures, which can be decomposed under relatively mild conditions. The hexahydrotriazine structure is an acid-sensitive six-membered heterocycle, and its derivatives can be decomposed into amines and formaldehyde when exposed to acidic solutions. Introducing it into thermosetting materials can fundamentally solve the scientific and technological problems of the difficulty of degradation and recycling of thermosetting materials.

[0005] Introducing degradable structures and biomass resources into polyurethane materials at the same time can solve the environmental ecological problems and sustainable development problems caused by polyurethane materials from the root. The patent "A quercetin-based degradable thermosetting polyurethane and its preparation method" (ZL 202210983423.4) discloses an acid-degradable polyurethane material based on biomass raw materials quercetin and hydroxyethyl hexahydro-s-triazine and its preparation method; the patent "A bio-based flame-retardant thermoplastic polyurethane material and its preparation method" (CN202210889262.2) discloses a flame-retardant polyurethane material with a high biomass content and its preparation method, but does not mention the degradation rate. New polyurethane materials that combine degradability and functionality are the development trend of sustainable materials. At present, research in this field has also begun to receive widespread attention, but there is still a need for continuous exploration in how to construct high-performance polyurethane material technologies with dual degradability such as biodegradability and chemical degradability, as well as other special functions. Summary of the invention

[0006] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a polycaprolactone-based functional polyurethane material, a preparation method and its application. The present invention proposes to introduce two degradable structures, hexahydrotriazine and polyester polyol, into the preparation of isosorbide-based polyurethane materials, thereby giving polyurethane chemical and biological multiple degradation properties. Secondly, the biomass raw material isosorbide is cheap, readily available, renewable, and environmentally friendly, which can improve the performance of the material in many aspects. In order to meet the requirements of biomedical use, the polyurethane material prepared by a non-catalytic system and polyester polyol has good biocompatibility and shape memory function, and is expected to be used in the matrix material of medical materials and flexible sensors.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0008] A polycaprolactone (PCL)-based functional polyurethane material, the structure of which contains two reversible dynamic covalent bonds, an ester group and a hexahydrotriazine ring; its strength and toughness are regulated by the ratio of the isosorbide rigid structure and the hydroxyethyl hexahydrotriazine cross-linking structure raw materials, and the synthesis reaction process is as follows.

[0009]

[0010] The present invention also provides a method for preparing a polycaprolactone (PCL)-based functional polyurethane material, comprising the following steps:

[0011] (1) under a nitrogen atmosphere, adding isosorbide and hydroxyl-terminated polycaprolactone polyol into a reaction vessel, stirring and mixing them uniformly in a molten state, and then adding a diisocyanate monomer dissolved in an organic solvent to perform prepolymerization to obtain an -NCO-terminated polyurethane prepolymer;

[0012] (2) Continue to add hydroxyethyl hexahydro-s-triazine to the polymerization system in step (1), continue to stir the reaction, then pour the reaction solution into a polytetrafluoroethylene mold for leveling, put it into a vacuum oven to evaporate the solvent and completely cure it to obtain a polyurethane film.

[0013] Furthermore, the organic solvent described in step (1) includes one or more of N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0014] Furthermore, in step (1), the molar ratio of isosorbide to polycaprolactone diol is 4:2, 3:2, 2:2, 1:2 or 0:2.

[0015] Furthermore, in step (1), the stirring temperature is 60° C. and the stirring time is 40 min; the diisocyanate monomer is added and reacted for 9-12 h, and the reaction temperature is 120° C.

[0016] Furthermore, the diisocyanate described in step (1) includes one or more of hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and isophorone diisocyanate.

[0017] Further, prepolymerization is performed to obtain a -NCO terminated polyurethane prepolymer, and then the temperature is reduced to 60°C.

[0018] Furthermore, in step (2), the continuous stirring reaction time is 30 minutes and the reaction temperature is 60°C.

[0019] Furthermore, in step (2), the molar ratio of isosorbide to hydroxyethyl hexahydro-s-triazine is 4:0, 3:1, 2:2, 1:3 or 0:4.

[0020] Furthermore, in step (2), the drying time in the vacuum oven is 20 hours at a temperature of 80°C.

[0021] Compared with the prior art, the present invention has many significant advantages, which are specifically manifested in the following aspects:

[0022] (1) In terms of mechanical properties and heat resistance, the polyurethane material of the present invention has made significant progress. This material not only has excellent tensile strength, elongation at break and wear resistance, and can maintain structural stability and integrity in various complex environments, but also its heat resistance is far superior to that of traditional polyurethane materials. Under high temperature conditions, it can still maintain good physical properties and is not prone to deformation or failure. Therefore, this polyurethane material is very suitable for use in medical materials and base materials of flexible sensors that have extremely high requirements for mechanical properties and heat resistance, such as pacemaker housings, artificial blood vessels, and wearable health monitoring devices, providing a more reliable and durable material option for the medical field.

[0023] (2) Biocompatibility is one of the important indicators for measuring the quality of medical materials. The polyurethane material of the present invention has excellent performance in biocompatibility, and the cell activity on the surface of the film is as high as 88% in a 72-hour experiment. This data fully proves that the material promotes cell growth and proliferation, and reduces the risk of immune response or rejection after the material is implanted in the body. Therefore, this polyurethane material has broad application prospects in the biomedical field, such as as a tissue engineering scaffold, wound dressing, and drug controlled release carrier, which can significantly improve the treatment effect and patient comfort.

[0024] (3) Shape memory function is an important property of polyurethane materials and is crucial for certain specific applications. The polyurethane material of the present invention has excellent performance in shape memory function, and its shape fixation rate (R f ) and shape recovery rate (R r ) are greater than 90%, which means that the material can quickly and accurately return to its original shape after being deformed by external force. This feature makes the material have great application potential in the fields of smart wearable devices, adaptive structures and soft robots, and can provide users with a more personalized and intelligent experience.

[0025] (4) In terms of degradation performance, the polyurethane material of the present invention also shows unique advantages. Compared with traditional polyurethane materials, this material has good chemical degradability and biodegradability. Under dilute acid conditions, it can be quickly and completely degraded, which provides convenience for the recycling and environmentally friendly utilization of the material. At the same time, after being placed in a biological enzyme buffer for 6 weeks, the material will also undergo obvious degradation, which shows that it also has good degradation performance in vivo, can reduce pollution to the environment and potential harm to organisms. This feature makes the material have a wider application prospect in the biomedical field, such as as a degradable implant, drug carrier and tissue engineering material, which can better meet the medical field's needs for environmental protection, safety and efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 ATR-FTIR spectra of polyurethane films prepared with different molar ratios of isosorbide and hydroxyethylhexahydro-s-triazine in Examples 1-5.

[0027] Figure 2 1 and 2 are stress-strain curves of the polyurethane films of Examples 1-5 (the embedded figure is a digital picture of PCL-PU2 of Example 2 lifting an object weighing approximately 20,000 times its own weight).

[0028] Figure 3 Schematic diagram of the shape memory process of the polyurethane film (PCL-PU2 of Example 2).

[0029] Figure 4 These are fluorescence microscopy images of L929 cells after being cultured on the surface of a polyurethane film (PCL-PU2 of Example 2) for 24 h, 48 h, and 72 h.

[0030] Figure 5 The film surfaces of the polyurethane series films prepared in Examples 1-5 are SEM images before and after 6 weeks of biodegradation.

[0031] Figure 6 The degradation phenomenon of the polyurethane series films prepared in Examples 1-5 in 2 mol / L phosphoric acid / ethanol solution.

[0032] In the figure, PCL-PU1, PCL-PU2, PCL-PU3, PCL-PU4, and PCL-PU5 correspond to the polyurethane series films prepared in Examples 1, 2, 3, 4, and 5, respectively. DETAILED DESCRIPTION

[0033] The present invention will be described in detail below in conjunction with specific embodiments and drawings of the present invention. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0034] In an embodiment of the present invention, a method for preparing a polycaprolactone-based functional polyurethane material comprises the following steps:

[0035] (1) under a nitrogen atmosphere, adding isosorbide and hydroxyl-terminated polycaprolactone polyol into a reaction vessel, stirring and mixing them uniformly in a molten state, and then adding a diisocyanate monomer dissolved in an organic solvent to perform prepolymerization to obtain an -NCO-terminated polyurethane prepolymer;

[0036] (2) Continue to add hydroxyethyl hexahydro-s-triazine to the polymerization system in step (1), continue to stir the reaction, then pour the reaction solution into a polytetrafluoroethylene mold for leveling, put it into a vacuum oven to evaporate the solvent and completely cure it to obtain a polyurethane film.

[0037] The organic solvent described in step (1) includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0038] In step (1), the molar ratio of isosorbide to polycaprolactone diol is 4:2, 3:2, 2:2, 1:2 or 0:2.

[0039] In step (1), the stirring temperature is 60° C. and the stirring time is 40 min. The diisocyanate monomer is added and reacted for 9-12 h at a reaction temperature of 120° C.

[0040] The diisocyanate described in step (1) includes one or more of hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and isophorone diisocyanate.

[0041] In step (1), the -NCO-terminated polyurethane prepolymer is obtained by prepolymerization, and then the temperature is reduced to 60°C.

[0042] The stirring reaction time in step (2) is 30 min and the reaction temperature is 60°C.

[0043] In step (2), the molar ratio of isosorbide to hydroxyethyl hexahydro-s-triazine is 4:0, 3:1, 2:2, 1:3 or 0:4.

[0044] In step (2), the drying time in a vacuum oven is 20 hours at a temperature of 80°C.

[0045] Technical principle of the present invention:

[0046] The ingenuity of the innovative preparation method of polycaprolactone (PCL)-based functional polyurethane material of the present invention lies in the precise control of the amount of raw materials used in each step and the careful optimization of process parameters, which not only ensures the excellence of material performance, but also achieves high efficiency and stability in the preparation process. The following is an in-depth analysis of the preparation method of the present invention, emphasizing the necessity of controlling the amount of raw materials and the order of steps, as well as the importance of optimizing process parameters.

[0047] 1. The necessity and importance of raw material dosage control

[0048] (1) Selection of diisocyanates: Different types of diisocyanates (such as hexamethylene diisocyanate, toluene diisocyanate, etc.) give polyurethane materials different chemical structures and physical properties. By selecting or mixing these monomers, the hardness, elasticity, heat resistance and chemical corrosion resistance of the material can be precisely controlled.

[0049] (2) The amount of hydroxyethyl hexahydrotriazine added: As a chain extender, the addition of hydroxyethyl hexahydrotriazine not only promotes the extension of the polyurethane chain, but also introduces additional functional groups, enhancing the crosslinking degree and thermal stability of the material. Adjusting its ratio with isosorbide can finely control the crosslinking density of the material, thereby affecting key performance indicators such as the elastic modulus, tensile strength and elongation at break of the material.

[0050] 2. The necessity of the order of steps cannot be changed

[0051] During the preparation process, the order of each step is carefully designed and cannot be changed at will. First, the mixing of isosorbide and polycaprolactone diol in a molten state ensures full contact and uniform distribution between the molecules of the two, laying a good foundation for subsequent chemical reactions. Then, a diisocyanate monomer dissolved in an organic solvent is added for prepolymerization. This step needs to be carried out under specific temperature and time conditions to ensure the formation of -NCO-terminated polyurethane prepolymers. If hydroxyethyl hexahydro-s-triazine is added in advance, it may interfere with the prepolymerization reaction and cause a decrease in material performance. Therefore, a strict order of steps is the key to ensuring material quality.

[0052] 3. Necessity and technical effect of optimizing process parameters

[0053] (1) Stirring temperature and time: During the melt mixing and prepolymerization stage, appropriate stirring temperature and time can accelerate the reaction process and promote the full reaction between the raw materials. For example, a stirring temperature of 60°C and a mixing time of 40 minutes ensure the uniform dispersion of the raw materials and provide good conditions for subsequent reactions. The prepolymerization reaction is carried out at 120°C for 9-12 hours, which ensures the full formation of the -NCO-terminated prepolymer, providing a guarantee for the performance of the final material.

[0054] (2) Drying conditions in a vacuum oven: After the reaction solution is poured into the mold, solvent evaporation and curing in a vacuum oven are key steps in the preparation of high-quality polyurethane films. A temperature of 80°C and a drying time of 20 h ensure effective removal of the solvent and avoid material degradation caused by high temperature, thus ensuring the flatness and structural integrity of the film.

[0055] In summary, through this series of finely controlled steps and optimized process parameters, the present invention not only successfully prepared PCL-based functional polyurethane materials with excellent performance, but also achieved unexpected technical effects, such as improving the biocompatibility, mechanical strength and thermal stability of the material, and broadening its application prospects in biomedicine, aerospace, automobile manufacturing and other fields. The innovation and practicality of this preparation method undoubtedly opened up a new direction for the research and development of PCL-based polyurethane materials.

[0056] In order to make the disclosure of the present invention more complete, it is described below through more specific embodiments.

[0057] Example 1

[0058] 4 g of hydroxyl-terminated polycaprolactone with a molecular weight of 2000 and an amount of 2 mmol and 0.45 g of isosorbide with an amount of 3 mmol were added to a three-necked flask, heated to 60°C, stirred for 40 min, 1.22 g of hexamethylene diisocyanate with an amount of 7.2 mmol was dissolved in 3 mL of N,N-dimethylformamide (DMF), added to the reaction system, heated to 120°C, and continued to react for 10 h to form a prepolymer, and a certain amount of DMF was added to control the viscosity of the reaction system; 0.10 g of hydroxyethyl hexahydro-s-triazine with an amount of 0.44 mmol was added to the above prepolymer for chain extension reaction. After reacting for 30 min, the reaction solution was poured into a polytetrafluoroethylene mold and dried at 80°C for 20 h to obtain a polycaprolactone-based multifunctional polyurethane material (denoted as: PCL-PU1) integrating biocompatibility, shape memory function and dual degradability.

[0059] The cell activity of L929 mouse fibroblasts on the polyurethane surface for 72 hours was 87.76%; the tensile strength of the polyurethane was 26.2MPa, and the elongation at break was 967%; the shape fixation rate (R f ) and shape recovery rate (R r ) were 96.50% and 92.48% respectively; the polyurethane was completely degraded in 2 mol / L phosphoric acid / ethanol solution for 20 h and lost 11.8% of its weight in 1 mg / mL lipase PBS buffer.

[0060] Example 2

[0061] In a 100ml three-necked flask, 4g of hydroxyl-terminated polycaprolactone with a molecular weight of 2000 and an amount of 2mmol and 0.30g of isosorbide with an amount of 2mmol were added, heated to 60°C and stirred for 40min, 1.22g of hexamethylene diisocyanate with an amount of 7.2mmol was dissolved in 3mL N,N-dimethylformamide (DMF) and added to the reaction system, the temperature was raised to 120°C, and the reaction was continued for 10h to form a prepolymer, and a certain amount of DMF was added to control the viscosity of the reaction system; 0.30g of hydroxyethyl hexahydro-s-triazine with an amount of 1.33mmol was added to the above prepolymer for chain extension reaction. After reacting for 30min, the reaction solution was poured into a polytetrafluoroethylene mold and dried at 80°C for 20h to obtain a polycaprolactone-based multifunctional polyurethane material (denoted as: PCL-PU2) integrating biocompatibility, shape memory function and dual degradability.

[0062] The cell activity of L929 mouse fibroblasts on the polyurethane surface for 72 hours was 88.69%; the tensile strength of the polyurethane was 31.4 MPa, and the elongation at break was 737%; the shape fixation rate (R f) and shape recovery rate (R r ) were 96.30% and 92.59% respectively; the polyurethane was completely degraded in 2 mol / L phosphoric acid / ethanol solution in 2.5 h, and lost 15.3% of its weight in 1 mg / mL lipase PBS buffer.

[0063] Example 3

[0064] 4 g of hydroxyl-terminated polycaprolactone with a molecular weight of 2000 and an amount of 2 mmol and 0.15 g of isosorbide with an amount of 1 mmol were added to a three-necked flask, heated to 60°C, stirred for 40 min, 1.22 g of hexamethylene diisocyanate with an amount of 7.2 mmol was dissolved in 3 mL of N,N-dimethylacetamide (DMAc), added to the reaction system, heated to 120°C, and continued to react for 10 h to form a prepolymer, and a certain amount of DMAc was added to control the viscosity of the reaction system; 0.46 g of hydroxyethyl hexahydro-s-triazine with an amount of 2 mmol was added to the above prepolymer for chain extension reaction. After reacting for 30 min, the reaction solution was poured into a polytetrafluoroethylene mold and dried at 80°C for 20 h to obtain a polycaprolactone-based multifunctional polyurethane material (denoted as: PCL-PU3) integrating biocompatibility, shape memory function and dual degradability.

[0065] The cell activity of L929 mouse fibroblasts on the polyurethane surface for 72 hours was 87.54%; the tensile strength of the polyurethane was 14.3 MPa, and the elongation at break was 617%; the shape fixation rate (R f ) and shape recovery rate (R r ) were 96.37% and 92.35% respectively; the polyurethane was completely degraded in 2 mol / L phosphoric acid / ethanol solution in 1.8 h, and lost 16.4% of its weight in 1 mg / mL lipase PBS buffer.

[0066] Example 4

[0067] 4 g of hydroxyl-terminated polycaprolactone with a molecular weight of 2000 and an amount of 2 mmol was added to a three-necked flask, heated to 60°C, and stirred for 40 min. 1.22 g of hexamethylene diisocyanate with an amount of 7.2 mmol was dissolved in 3 mL of N,N-dimethylformamide (DMF) and added to the reaction system. The temperature was raised to 120°C, and the reaction was continued for 10 h to form a prepolymer. A certain amount of DMF was added to control the viscosity of the reaction system. 0.61 g of hydroxyethyl hexahydro-s-triazine with an amount of 2.67 mmol was added to the above prepolymer for chain extension reaction. After reacting for 30 min, the reaction solution was poured into a polytetrafluoroethylene mold and dried at 80°C for 20 h to obtain a polycaprolactone-based multifunctional polyurethane material (denoted as: PCL-PU4) integrating biocompatibility, shape memory function and dual degradability.

[0068] The cell activity of L929 mouse fibroblasts on the polyurethane surface for 72 hours was 88.32%; the tensile strength of the polyurethane was 15.3 MPa, and the elongation at break was 557%; the shape fixation rate (R f ) and shape recovery rate (R r ) were 95.85% and 92.43% respectively; the polyurethane was completely degraded in 2 mol / L phosphoric acid / ethanol solution in 7.5 h, and lost 28.8% of its weight in 1 mg / mL lipase PBS buffer.

[0069] Example 5

[0070] In a three-necked flask, add 4g of hydroxyl-terminated polycaprolactone with a molecular weight of 2000 and a substance amount of 2mmol and 0.60g of isosorbide with a substance amount of 4mmol, heat to 60℃, stir for 40min, dissolve 1.22g of hexamethylene diisocyanate with a substance amount of 7.2mmol in 3mLN,N-dimethylformamide (DMF), add to the reaction system, heat to 80℃, continue to react for 12h, form a prepolymer, add a certain amount of DMF to control the viscosity of the reaction system. Without adding hydroxyethyl hexahydro-s-triazine, directly pour the above reaction solution into a polytetrafluoroethylene mold, dry at 80℃ for 20h, and obtain a polycaprolactone-based multifunctional polyurethane material (denoted as: PCL-PU5) that integrates biocompatibility, shape memory function and dual degradability.

[0071] The cell activity of L929 mouse fibroblasts on the polyurethane surface for 72 hours was 88.13%; the tensile strength of the polyurethane was 13.5 MPa, and the elongation at break was 766%; the shape fixation rate (R f ) and shape recovery rate (R r) were 96.14% and 92.87% respectively; the polyurethane was completely degraded in 2 mol / L phosphoric acid / ethanol solution for 48 h and lost 2.7% of its weight in 1 mg / mL lipase PBS buffer.

[0072] Example 6

[0073] In a three-necked flask, 4 g of hydroxyl-terminated polycaprolactone with a molecular weight of 2000 and an amount of 2 mmol and 0.30 g of isosorbide with an amount of 2 mmol were added, heated to 60°C and stirred for 40 min, 1.25 g of toluene diisocyanate with an amount of 7.2 mmol was dissolved in 3 mL of N,N-dimethylacetamide (DMAc) and added to the reaction system, the temperature was raised to 120°C, the reaction was continued for 12 h to form a prepolymer, and a certain amount of DMF was added to control the viscosity of the reaction system; 0.30 g of hydroxyethyl hexahydro-s-triazine with an amount of 1.33 mmol was added to the above-mentioned prepolymer for chain extension reaction. After reacting for 30 min, the reaction solution was poured into a polytetrafluoroethylene mold and dried at 80°C for 20 h to obtain a polycaprolactone-based multifunctional polyurethane material (denoted as: PCL-PU6) integrating biocompatibility, shape memory function and dual degradability.

[0074] The cell activity of L929 mouse fibroblasts on the polyurethane surface for 72 hours was 86.67%; the tensile strength of the polyurethane was 33.6MPa, and the elongation at break was 569%; the shape fixation rate (R f ) and shape recovery rate (R r ) were 94.45% and 90.76% respectively; the polyurethane was completely degraded in 2 mol / L phosphoric acid / ethanol solution in 4.5 h, and lost 13.7% of its weight in 1 mg / mL lipase PBS buffer.

[0075] Example 7

[0076] In a three-necked flask, 4 g of hydroxyl-terminated polycaprolactone with a molecular weight of 2000 and an amount of 2 mmol and 0.30 g of isosorbide with an amount of 2 mmol were added, heated to 60°C and stirred for 40 min, 1.80 g of diphenylmethane diisocyanate with an amount of 7.2 mmol was dissolved in 3 mL of N-methylpyrrolidone (NMP) and added to the reaction system, the temperature was raised to 120°C, the reaction was continued for 10 h to form a prepolymer, and a certain amount of DMF was added to control the viscosity of the reaction system; 0.30 g of hydroxyethyl hexahydro-s-triazine with an amount of 1.33 mmol was added to the above-mentioned prepolymer for chain extension reaction. After reacting for 30 min, the reaction solution was poured into a polytetrafluoroethylene mold and dried at 80°C for 20 h to obtain a polycaprolactone-based multifunctional polyurethane material (denoted as: PCL-PU7) integrating biocompatibility, shape memory function and dual degradability.

[0077] The cell activity of L929 mouse fibroblasts on the polyurethane surface for 72 hours was 88.15%; the tensile strength of the polyurethane was 34.8 MPa, and the elongation at break was 541%; the shape fixation rate (R f ) and shape recovery rate (R r ) were 93.83% and 90.22% respectively; the polyurethane was completely degraded in 2 mol / L phosphoric acid / ethanol solution for 5 h and lost 13.3% of its weight in 1 mg / mL lipase PBS buffer.

[0078] Example 8

[0079] In a three-necked flask, 4 g of hydroxyl-terminated polycaprolactone with a molecular weight of 2000 and an amount of 2 mmol and 0.30 g of isosorbide with an amount of 2 mmol were added, heated to 60°C and stirred for 40 min, 1.60 g of isophorone diisocyanate with an amount of 7.2 mmol was dissolved in 3 mL of N,N-dimethylformamide (DMF) and added to the reaction system, the temperature was raised to 120°C, the reaction was continued for 9 h to form a prepolymer, and a certain amount of DMF was added to control the viscosity of the reaction system; 0.30 g of hydroxyethyl hexahydro-s-triazine with an amount of 1.33 mmol was added to the above prepolymer for chain extension reaction. After reacting for 30 min, the reaction solution was poured into a polytetrafluoroethylene mold and dried at 80°C for 20 h to obtain a polycaprolactone-based multifunctional polyurethane material (denoted as: PCL-PU8) integrating biocompatibility, shape memory function and dual degradability.

[0080] The cell activity of L929 mouse fibroblasts on the polyurethane surface for 72 hours was 87.85%; the tensile strength of the polyurethane was 33.1 MPa, and the elongation at break was 635%; the shape fixation rate (R f) and shape recovery rate (R r ) were 95.13% and 91.47% respectively; the polyurethane was completely degraded in 2 mol / L phosphoric acid / ethanol solution in 3.5 h, and lost 14.1% of its weight in 1 mg / mL lipase PBS buffer.

[0081] The performance test results of each polyurethane sample in the above examples show that the isosorbide-based polyurethane prepared based on polycaprolactone and hexahydrotriazine structures all exhibit high mechanical strength, good shape memory function, and also have dual degradation properties of complete acid hydrolysis and biodegradation. In addition, Examples 1-5 show that by adjusting the ratio of rigid structure and cross-linked structure raw materials in the polyurethane structure, the strength and toughness of the material can be adjusted and the biodegradability can be improved; by comparing Examples 2, 6-8, it can be seen that changing the diisocyanate structure, that is, increasing the rigidity of the polyurethane hardness structure, helps to improve the mechanical strength of the polyurethane.

[0082] The following is attached Figure 1-6 , further illustrating the structure and properties of the polyurethane samples of Examples 1-5.

[0083] See also Figure 1 , the raw materials and polyurethane films prepared with different molar ratios of isosorbide and hydroxyethyl hexahydro-s-triazine in Examples 1-5 were characterized by infrared FTIR. First, hexamethylene diisocyanate (HDI) showed obvious isocyanate characteristic absorption peaks, while in the infrared spectrum of the polyurethane film, the -NCO characteristic absorption peak completely disappeared, and the excess isocyanate groups had been completely consumed, indicating a thorough polycondensation reaction. Secondly, the hydroxyl peaks of isosorbide, hydroxyethyl hexahydro-s-triazine and polycaprolactone (PCL) in the reaction raw materials were completely reacted. The peak positions of the infrared characteristic absorption peaks of the polyurethane series films are consistent, which indicates that the synthesized polyurethanes have similar structures.

[0084] See also Figure 2 , the mechanical properties of the polyurethane series films of Examples 1-5 were tested. It can be seen from the figure that the tensile strength of the samples shows a trend of first increasing and then decreasing with the increase of the hexahydrotriazine content. Compared with the polyurethane without hexahydrotriazine, the tensile strength of the polyurethane with hexahydrotriazine added is significantly improved. However, as the hexahydrotriazine content continues to increase, the tensile strength of the material will reach a threshold, and the cross-linking density will basically reach saturation. Excessive hexahydrotriazine leads to a decrease in tensile strength. In addition, due to the reduction of isosorbide in the system, the mechanical properties are also easily reduced due to the lack of rigid groups that serve to strengthen the material in the system. On the whole, the polyurethane film PCL-PU2 prepared in Example 2 has good mechanical properties (tensile strength of 31.13MPa, elongation at break of 736.33%).

[0085] See also Figure 3 , the polyurethane film PCL-PU2 prepared in Example 2 was cut into dumbbell-shaped splines, and the splines were heated to 37°C. The crystalline area of ​​the polyurethane film was in a molten state, and the fluidity of the molecular chain was good, so that it was fully softened and stretched to 200%. Secondly, it was kept at -5°C for 5 minutes to fix the temporary shape. After being placed at room temperature for 30 minutes, it was found that the material could maintain its shape well. This is because the soft segment crystallized under the action of stress and low temperature, the stress was fixed in the material, the molecular chain could not move, and the material was fixed in a temporary shape. Heating the sample to 37°C accelerated the movement of the molecular chains. The melting of the soft segment crystals caused the stress inside the material to be released, and the material was able to basically return to its initial shape. According to the shape fixation rate (R f ) and shape recovery rate (R r ) formula, the R of the polyurethane film prepared in Example 2 f and R r 96.30% and 92.59% respectively.

[0086] See also Figure 4 , which is a fluorescence microscope image of the growth of L929 mouse fibroblasts after culturing on the surface of the polyurethane film PCL-PU2 material prepared in Example 2 for 24h, 48h and 72h. It can be seen that under the action of the living cell stain Calcein-AM, it is easy to penetrate the living cell membrane. When it enters the cytoplasm, esterase will hydrolyze it into Calcein and leave it in the cell, emitting strong green fluorescence. Within three time periods, the cells can be well spread on the surface of the polyurethane film material and are well distributed. The cell morphology is healthy, the edges are clear and complete, and it is spindle-shaped. The above results show that the surface of the material is suitable for cell growth and has excellent biocompatibility.

[0087] See also Figure 5 , which are the surface SEM images of the polyurethane series films prepared in Examples 1-5 after 0 and 6 weeks of degradation, it can be seen that the surface of the samples before degradation is smooth and flat. With the increase of the amount of hydroxyethyl hexahydro-s-triazine, the surface of the samples after degradation becomes rough, and even obvious cracks appear. As mentioned above, the acidic carboxyl autocatalytic reaction gradually increases the degradation rate of the film. The surface of the polyurethane film PCL-PU1 is relatively rough, while the surface of the polyurethane film PCL-PU4 has obvious grooves and voids, and its degradation degree is more severe. The change in the surface morphology of the film is consistent with the law of macroscopic mass loss.

[0088] See also Figure 6, five polyurethane films of different proportions were placed in a 2mol / L phosphoric acid-ethanol solution for degradation experiments. It can be found that the polyurethane film PCL-PU5 prepared in Example 5 has the longest degradation time. This is because the film does not contain hydroxyethyl hexahydro-s-triazine rings, and the degradation time in a slightly acidic solution is long, but it belongs to a thermoplastic polyurethane material, and its molecules are basically linear. It is a type of soluble material, so it can also be completely degraded. The degradation time of films with other proportions shortens with the increase of the hydroxyethyl hexahydro-s-triazine content and the concentration of the phosphoric acid ethanol solution in the system. The polyurethane film PCL-PU2 prepared in Example 2, which has better thermal stability and tensile properties, can be completely degraded in a 2mol / L phosphoric acid ethanol solution at room temperature in only 2.2h.

[0089] The above-mentioned implementation modes are preferred implementation modes of a part of the present invention and are not any form of limitation to the present invention. Any other modifications, equivalent changes, modifications and simplifications made to the above implementation modes based on the technical essence of the present invention are within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a polycaprolactone-based functional polyurethane material, characterized in that: The following steps are involved: (1) under a nitrogen atmosphere, adding isosorbide and hydroxyl-terminated polycaprolactone polyol into a reaction vessel, stirring and mixing them uniformly in a molten state, and then adding a diisocyanate monomer dissolved in an organic solvent to perform prepolymerization to obtain an -NCO-terminated polyurethane prepolymer; (2) Continue to add hydroxyethyl hexahydro-s-triazine to the polymerization system in step (1), continue to stir the reaction, then pour the reaction solution into a polytetrafluoroethylene mold for leveling, put it into a vacuum oven to evaporate the solvent and completely cure it to obtain a polyurethane film.

2. The method for preparing a polycaprolactone-based functional polyurethane material according to claim 1, characterized in that: The organic solvent described in step (1) includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

3. The method for preparing a polycaprolactone-based functional polyurethane material according to claim 1, characterized in that: In step (1), the molar ratio of isosorbide to polycaprolactone diol is 4:2, 3:2, 2:2, 1:2 or 0:

2.

4. The method for preparing a polycaprolactone-based functional polyurethane material according to claim 1, characterized in that: In step (1), the stirring temperature is 60° C. and the stirring time is 40 min. The diisocyanate monomer is added and reacted for 9-12 h at a reaction temperature of 120° C.

5. The method for preparing a polycaprolactone-based functional polyurethane material according to claim 1, characterized in that: The diisocyanate described in step (1) includes one or more of hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and isophorone diisocyanate.

6. The method for preparing a polycaprolactone-based functional polyurethane material according to claim 1, characterized in that: The stirring reaction time in step (2) is 30 min and the reaction temperature is 60°C.

7. The method for preparing a polycaprolactone-based functional polyurethane material according to claim 1, characterized in that: In step (2), the molar ratio of isosorbide to hydroxyethyl hexahydro-s-triazine is 4:0, 3:1, 2:2, 1:3 or 0:

4.

8. The method for preparing a polycaprolactone-based functional polyurethane material according to claim 1, characterized in that: In step (2), the drying time in a vacuum oven is 20 hours at a temperature of 80°C.

9. A polycaprolactone-based functional polyurethane material prepared according to the method according to any one of claims 1 to 8.

10. An application of the polycaprolactone-based functional polyurethane material according to claim 9, characterized in that: Used in matrix materials including medical materials and flexible sensors.

Citation Information

Patent Citations

  • Degradable shape memory polyurethane material and preparation method and application thereof

    CN106146777A

  • Polyurethane with shape memory function and preparation method thereof

    CN109880054A

  • Quercetin-based degradable thermosetting polyurethane and preparation method thereof

    CN115505085A

  • Self-repairable, repeatedly-processed and degradable polyurethane material based on multi-bond action and preparation method of self-repairable, repeatedly-processed and degradable polyurethane material

    CN118930793A

Cited By

  • Bio-based degradable polyurethane material and preparation method thereof

    CN120518838A